International trade and Covid‐19: City‐level evidence from China's lockdown policy. (22nd August 2021) - Pei, Jiansuo; de Vries, Gaaitzen; Zhang, Meng
Abstract: This paper examines the impact of Covid‐19 lockdowns on exports by Chinese cities. We use city‐level export data at a monthly frequency from January 2018 through April 2020. Differences‐in‐differences estimates suggest cities in lockdown experienced a ceteris paribus 34 percentage points reduction in the year‐on‐year growth rate of exports. The lockdown impacted the intensive and extensive margin, with higher exit and lower new entry into foreign markets. The drop in exports was smaller in (i) coastal cities; (ii) cities with better‐developed ICT infrastructure; and (iii) cities with a larger share of potential teleworkers. Time‐sensitive and differentiated goods experienced a more pronounced decline in export growth. Global supply chain characteristics matter, with more upstream products and industries that had accumulated larger inventories experiencing a smaller decline in export growth. Also, products that relied more on imported (domestic) intermediates experienced a sharper (flatter) slowdown in export growth. The rapid recovery in cities' exports after lockdowns were lifted suggests the policy was cost‐effective in terms of its effects on trade.